2018
DOI: 10.18665/sr.307005
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Advising Analytics to Promote Success (MAAPS): Evaluation Findings from the First Year of Implementation

Abstract: Ithaka S+R provides research and strategic guidance to help the academic and cultural communities serve the public good and navigate economic, demographic, and technological change. Ithaka S+R is part of ITHAKA, a not-for-profit organization that works to advance and preserve knowledge and to improve teaching and learning through the use of digital technologies. Artstor, JSTOR, and Portico are also part of ITHAKA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…And Georgia State University (GSU), whose predictive model included factors that impede a student's chances of success, increased semester‐to‐semester retention by 5%, reduced time‐to‐degree rates, and saved the state's taxpayers nearly five million dollars (University Innovation Alliance, n.d.; Kamenetz, ). In contrast to the findings at these institutions, a multi‐institutions study of advising analytics found no significant impacts, and it should be noted that impacts—positive or negative—should not be attributed to just the use of an analytic tool and may arise due to investments in personnel, other resources, and changes in policy, among other things (Alamuddin, Rossman, & Kurzweil, ).…”
Section: Educational Data Mining and Learning Analyticsmentioning
confidence: 74%
“…And Georgia State University (GSU), whose predictive model included factors that impede a student's chances of success, increased semester‐to‐semester retention by 5%, reduced time‐to‐degree rates, and saved the state's taxpayers nearly five million dollars (University Innovation Alliance, n.d.; Kamenetz, ). In contrast to the findings at these institutions, a multi‐institutions study of advising analytics found no significant impacts, and it should be noted that impacts—positive or negative—should not be attributed to just the use of an analytic tool and may arise due to investments in personnel, other resources, and changes in policy, among other things (Alamuddin, Rossman, & Kurzweil, ).…”
Section: Educational Data Mining and Learning Analyticsmentioning
confidence: 74%
“…Students also described how interactions with MAAPS advisors were notably different from primary advisors, praising proactive communications, the ease of scheduling a one-on-one appointment, and that MAAPS appointments took a more developmental approach (Schwebel et al, 2008;Varney, 2013). Such positive impressions support claims that proactive advising is a practice that can facilitate students' engagement with their institution (Valentine & Price, 2021), help them navigate hardships at key junctures in their college experience (Varney, 2013), and that this resource may be especially beneficial to students from low-SES backgrounds depending on how the program is designed and administered (Alamuddin et al, 2018).…”
Section: Discussionmentioning
confidence: 61%
“…A prior randomized control trial (RCT) study compared academic achievement measures of students who were offered the MAAPS intervention (in addition to the university's primary academic advising services) with students who only worked with primary advisors. This RCT study showed no significant differences between groups at most institutions (Alamuddin et al, 2018(Alamuddin et al, , 2019. However, student surveys and focus groups suggested some students gained beneficial skills and experiences (Alamuddin et al, 2019).…”
Section: Nacada Journalmentioning
confidence: 66%
See 1 more Smart Citation
“…Third, administrators could adopt data-driven approaches to student improvement by introducing tracking systems that include predictive analytics to help better target interventions, though there is mixed evidence on the efficacy of such data-driven approaches in terms of improving student outcomes (Milliron, Malcom, and Kil 2014;Alamuddin, Rossman, and Kurzweil 2018;Main and Griffith 2019). Finally, administrators could attempt to alter the number and composition of entering students, either by altering recruiting efforts or by explicitly changing admission requirements.…”
Section: Conceptual Frameworkmentioning
confidence: 99%